E-readiness towards mobile learning at Kolej Yayasan Melaka / Muhamad Rizal Mohamed Razali - Mohamed Razali, Muhamad Rizal (2005)
With respect to the mobile industry's explosive growth, mobile technology does hold a strong effect on learning processes; from traditional learning to mobile learning (M-learning).Traditional learning is normally held in a classroom where teachers present learning materials to various groups of students. Meanwhile, M-learning uses all types of applications (found in the e-learning concept) that are designed and intended for mobile communication devices such as notebooks, mobile phones, hand-held computers and PDAs. The M-learning education process is undoubtedly more flexible as students can learn continuously regardless of time or place. Today, many universities and private colleges are trying to implement M-learning. To implement M-learning, an organisation needs to invest in a diverse array of mobile communication technologies, mobile devices and training costs. After initial investments are put in to set up the M-learning infrastructure, some projects may fail or ultimately become useless because staff and students are sometimes not ready to change the paradigm of learning from traditional learning to M-learning. To prevent this situation, organisations need to conduct surveys on e-readiness towards mobile learning in order to ensure that they are ready for this new - and almost radical - paradigm of learning. This project focuses on e-readiness towards mobile learning at Kolej Yayasan Melaka (KYM). This organisation needs to focus on choosing the right devices and suitable communication technologies as well as the matter of changing its learning paradigm when it comes to implementing M-learning. Questionnaires were distributed to 100 individuals at KYM to determine whether the staff,' students and the entire organisation is ready to implement M-learning. Findings from the survey proved that KYM's community shows great interest when it comes to the M-learning concept. However, from the technology and knowledge aspects, they are still not ready. This paper also highlights the problems faced during this independent study. The respondents number only 100, while in actuality, in order to get the best survey, more than 100 respondents would be ideal. This is due to the tight time frame given (three months). Further analyses focus on pedagogy, technology and security measures. In general, an organisation would need to campaign the benefits of using wireless networks and conduct short courses on how to use M-learning applications to encourage those involved to own their personal mobile devices. An organisation must also have long-term plans when it comes to setting up the M-learning concept.